PENDAMPINGAN SERTIFIKASI HALAL UMKM MELALUI "HALAL SELF-DECLARE": STUDI DI AFLAHA MART, PLERET PONDOK PESANTREN MUHAMMADIYAH, YOGYAKARTA - Maesyaroh, Maesyaroh; Martiana, Andri; Della Agustin, Putri (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
The government, through the Halal Product Guarantee Agency (BPJPH), provides easy access to the public, especially micro businesses, so that they can obtain a free halal certificate, namely the existence of a Halal Self Declaration. Halal self-declaration is an effort to certify halal through statements by business actors supervised by the Halal Inspection Agency. The purpose of this activity is to educate and assist food suppliers in the Aflaha Mart MBS Pleret canteen for the realization of the halal industry, especially in the food sector, so that it is safe and thayib consumed by consumers. The target of the halal self-declaration program in this activity is the suppliers of processed food at the Aflaha Mart canteen of MBS Pleret. The problem faced by partners is that, currently, there is not a single halal-certified food, even though halal certification is an obligation for business actors. The method of this activity is to socialize the importance of halal certification and assist with the mechanism for applying for halal certification through halal self. The results of the service show that after the pre-test and post-test treatments, the food business actors have knowledge of halal food, which is allowed by Islam, but they do not understand the mechanism for applying for halal certification. At least with this activity, business actors have increased their understanding regarding the management of halal certification through â€œhalal self-declareâ€.